Use of the Health Belief Model for the Assessment of Public Knowledge and Household Preventive Practices in Karachi, Pakistan, a Dengue-Endemic City. - Taranum Ruba Siddiqui; Saima Ghazal; Safia Bibi; Waquaruddin Ahmed; Shaimuna Fareeha Sajjad (Public Library of Science (PLoS), 2016)
Prevention is most effective in reducing dengue infection risk, especially in endemic countries like Pakistan. Evaluation of public awareness and health beliefs regarding dengue fever (DF) is important for devising disease control strategies. This study assessed dengue knowledge, health beliefs, and preventive practices against DF in different socioeconomic groups of Karachi, Pakistan.In this community-based cross-sectional study, 6 randomly selected towns were visited, 2 persons (man and woman) per household were interviewed using a structured questionnaire, and household practices were observed. Information regarding DF was shared through a printed pamphlet. Multivariate logistic regression analysis of variables associated with dengue knowledge and practices was conducted.We interviewed 608 Karachi residents (mean age: 33.2 ± 13.35 years); 7.7%, 71.9%, and 20.4% had a high, middle, and low socioeconomic status, respectively. The mean knowledge score was 6.4 ± 2.10 out of 14. The mean preventive practices score was 9 ± 1.8 out of 17. Predictors of dengue knowledge were perceived threat (odds ratio [OR] = 1.802; 95% confidence interval [CI] = 1.19-2.71; p = 0.005), self-efficacy (OR = 2.910; 95% CI = 1.77-4.76; p = 0.000), and television as an information source (OR = 3.202; 95% CI = 1.97-5.17; p = 0.000). Predictors of dengue preventive practices were perceived threat (OR = 1.502; 95% CI = 1.02-2.19; p = 0.036), self-efficacy (OR = 1.982; 95% CI = 1.34-2.91; p = 0.000), and dengue knowledge (OR = 1.581; 95% CI = 1.05-2.37; p = 0.028).Public knowledge about DF is low in Karachi. Knowledge, threat perception, and self-efficacy are significant predictors of adequate dengue preventive practices. Prevention and control strategies should focus on raising awareness about dengue contraction risk and severity through television. Health messages should be designed to increase individual self-efficacy.